Prognozowanie transferów na rynku otwartych funduszy emerytalnych - Chybalski, Filip (Forecasting Transfers on the Market of Open Pension Funds, 2006)
The main aim of the article is the proposition of time series model which could be applied to predict the matrix of transfers on market of open pension funds. This matrix consist on n2 elements (n - number of open pension funds) describing the flow of people between funds. Today we have 15 OFE so the number of predicted variables is equal to 225 -15 =210, because x*ii = 0. Presented model is very universal because it can be applied to the prediction time series with trend and constant level which is the most important advantage of it. The forecast for period T is estimated by adding the combination of growths from last k periods multiplied by wages to the empirical value of the variable from period T - 1. The optimal wages are found by use of the criterion of minimal ex post error.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 187-196